(untitled) - Forouzan, Behrouz A. (Boston, 2006)
TCP/IP Protocol Suite teaches students and professionals, with no prior knowledge of TCP/IP, everything they need to know about the subject. This comprehensive book uses hundreds of figures to make technical concepts easy to grasp, as well as many examples, which help tie the material to the real-world.
Keywords: TCP/IP (Computer network protocol),TCP/IP ( cổng kết nối máy tính)